Accelerated simulation of hierarchical military operations with tabulation technique. Issue 1 (1st February 2016) - Bae, J W; Kim, J H; Moon, I-C; Kim, T G
Abstract: Recently, a challenge in defence modelling and simulation is that simulating a satisfactory number of scenarios often requires an infeasible runtime. This paper resolves this challenge by utilizing a tabulation technique that encourages reuses of the previous simulation results in hierarchical models. For example, a mission-level model may contain a number of similar engagement scenarios that must be executed multiple times by an engagement-level model. Therefore, we collapse the multiple similar executions into a single simulation run while verifying the statistical stability in the output distribution. This reuse is supported by adapting the tabulation technique to hierarchical models with the extension of an interpolation in matching the lower abstractions. An application in the naval air defence domain shows that the simulation is speeded up a maximum of seven times, while producing statistically identical simulation results with few increments in the variance.